Association between dietary caffeine, coffee, and tea consumption and depressive symptoms in adults: A systematic review and dose-response meta-analysis of observational studies - Torabynasab, Kimia; Shahinfar, Hossein; Payandeh, Nastaran; Jazayeri, Shima (Frontiers in Nutrition, 2023)
Background: Accumulating evidence has been reported regarding the association of dietary caffeine, coffee, and tea intake on depressive symptoms, however, findings are controversial. Purpose: We aimed to assess the association between dietary caffeine, coffee, tea consumption and depressive symptoms in adults. Methods: The databases of PubMed and Scopus were searched to December 2021. Data were extracted and rated the certainty of evidence using GRADE approach by 2 investigators from identified studies. Random-effects models were applied to estimate the relative risks (RRs) and 95% CIs. Dose-response associations were modeled by a one-stage weighted mixed-effects meta-analysis. Results: 29 eligible studies include a total of 422586 participants. Comparing highest with the lowest category in cohort studies, there was an inverse association between intake of coffee and depressive symptoms (RR:0.89, 95%CI:0.82-0.95; I2 =63.7%, GRADE=low). A 240 ml/d increment in coffee intake was associated to the 4% lower risk of depression (RR: 0.96, 95%CI: 0.95, 0.98; I2 = 22.7%). Comparing highest with the lowest category in cohort studies, caffeine intake was inversely associated with depressive symptoms (RR:0.86, 95%CI:0.79, 0.93; I2 =0.0%, GRADE=moderate). No significant relationship was detected between dietary intakes of tea and depressive symptoms.